Numerical and Experimental Investigations of the Cavitating Behavior of an Inducer. (2004) - Bakir, F.; Rey, R.; Gerber, A. G.; Belamri, T.; Hutchinson, B.
Abstract : A robust CFD model is described, suitable for general three-dimensional flows with extensive cavitation at large density ratios. The model utilizes a multiphase approach, based on volume-scalar-equations, a truncated Rayleigh-Plesset equation for bubble dynamics, and specific numerical modifications (in a finite-volume solution approach) to promote robust solutions when cavitation is present. The model is implemented in the CFD software CFX TASCflow 2.12. The validation of the model was done on an inducer designed and tested at LEMFI. First, The physical model and the numerical aspects are described. Then, the experimental and numerical methodologies, at cavitating regime, are presented. Finally, for several flow rates, the comparisons between experimental and simulated results on the overall performances, head drop and cavitation figures, are discussed. For a range of flow rates, good agreement between experiment and prediction was found.